2021
DOI: 10.1093/milmed/usab315
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometrics and Body Composition Predict Physical Performance and Selection to Attend Special Forces Training in United States Army Soldiers

Abstract: Introduction Anthropometrics and body composition characteristics differentiate many types of athletes and are related to performance on fitness tests and tasks in military personnel. Soldiers competing to enter elite units must demonstrate physical fitness and operational competence across multiple events. Therefore, this study determined whether anthropometrics and body composition predicted physical performance and selection for special forces training among soldiers attending the rigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 24 publications
3
18
0
1
Order By: Relevance
“…Although our hypothesis was related to LBM, we found that lower %BF was strongly correlated with higher scores on all ACFT events, except the PLK. Our findings are consistent with military studies that report lower %BF is associated with better 2MR [ 7 , 8 ] and push-up scores [ 8 ]. Despite the Army’s shift to the ACFT that is more focused on strength, power, speed, and agility; our investigation indicates that %BF has proven to be an important contributor to success on events that assess these physical domains, and therefore, performance of combat-relevant tasks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although our hypothesis was related to LBM, we found that lower %BF was strongly correlated with higher scores on all ACFT events, except the PLK. Our findings are consistent with military studies that report lower %BF is associated with better 2MR [ 7 , 8 ] and push-up scores [ 8 ]. Despite the Army’s shift to the ACFT that is more focused on strength, power, speed, and agility; our investigation indicates that %BF has proven to be an important contributor to success on events that assess these physical domains, and therefore, performance of combat-relevant tasks.…”
Section: Discussionsupporting
confidence: 93%
“…While LBM was correlated with HRPU scores, controlling for %BF attenuated the association between LBM and HRPU performance. Similarly, Farina et al [ 8 ] found that lower %BF predicted better performance on the push-up event, whereas LBM did not.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Una reciente revisión de la literatura (Farina et al, 2021) reveló que la composición corporal es un predictor del rendimiento físico que puede ser modificado, de esta manera; y es así que una buena composición corporal permite una mejor preparación para las exigencias de los cursos militares que requieren de altas demandas físicas. Al comparar la talla de soldados de distintos ejércitos se aprecia que los soldados serbios (180,2 cm), finlandeses (180,0 cm) y montenegrinos (181,7 cm) serían los más altos, mientras que los canadienses (178,0 cm), los belgas (177,5 cm), los estadounidenses (176,0 cm) y los turcos (173,0 cm) son los más bajos (Spalevic et al, 2021).…”
Section: Discussionunclassified
“…The observed changes indicate that the current US Army IMT environment promotes anabolism and supports positive adaptations to physical training in new military recruits independent of dietary intake. These findings are important due to the association between body composition and physical performance (Farina et al, 2021) as well as injury risk (Anderson et al, 2015; Jones et al, 2017) in various military populations.…”
Section: Discussionmentioning
confidence: 99%